Handbook of global economic policy - Nagel, Stuart S., 1934- (Public administration and public policy ;, 2000)
A handbook of global economic policy. It develops practical, non-ideological solutions to the problems, and tests its solution's feasibility through economic, administrative, political, psychological, legal, international and technological obstacles.